Finnish video games : a history and catalog - Kuorikoski, Juho (McFarland & Company, Inc., 2015)
In the past three decades Finland's video game industry has become the backbone of Finnish cultural export. Angry Birds and Clash of Clans are dominating sales around the world and the small Nordic nation has become a gaming superpower. Drawing on more than 60 interviews, this book covers the Finnish video game phenomenon as told by the people behind its success. The history of the industry is documented in detail for the first time. Two hundred game reviews are included, presenting the best (and worst) of commercial video games made in Finland.